# Solve x^{2} - 12x + 5 = 0 using the completing-the-square method.

**Solution:**

Given x^{2} - 12x + 5 = 0

This is similar to quadratic equation ax^{2} + bx + c = 0

Add (b/2)^{2} on both sides

Here b = -12

Add (-12/2)^{2} = (-6)^{2 }= 36

x^{2} - 12x + 36 = -5 + 36

x^{2} - 2(x)(6) + 6^{2} = 31

This is in the form a^{2} - 2ab + b^{2} = (a - b)^{2}

(x - 6)^{2} = 31

x - 6 = ±√31

x = ±√31 + 6

Therefore, the solution is x = 6 ± √31

## Solve x^{2} - 12x + 5 = 0 using the completing-the-square method.

**Summary:**

Using the completing-the-square method for x^{2} - 12x + 5 = 0, we get a solution as x = 6 ± √31.

Math worksheets and

visual curriculum

visual curriculum